Prevention of Employment-Based Human Trafficking: A Comparative Review Between Indonesia and South Korea - Wijaya, Vivian; Setiawan, Peter Jeremiah (Jurnal Hukum Replik, 2024)
One of the biggest exporters of migrant laborers from Asia is Indonesia. It is common for migrant workers to be exploited in a number of ways, both legal and illicit. In 2020, women were the majority of the detected victims, with a percentage of 58% compared to the percentage of men at 18%. Based on Global Organized Crime Index data on Ranking by Human Trafficking, the Republic of Korea is ranked 129th out of 193 nations worldwide and 35th out of 46 countries in Asia. This paper will examine the regulation of prevention of persons and the comparison of prevention of persons regulations in Indonesia and the Republic of Korea. The methodology of this research is used Normative-Empirical and uses prescriptive analysis. The approach used is the statute approach. The prevention of human trafficking in Indonesia is a violation of human rights that arises as a result of exploitation and human trafficking. In the comparison of human trafficking regulations between Indonesia, namely Law Number 21 of 2007 with the Republic of Korea (Act on Prevention of Human Trafficking and Protection of Victims) there are numerous regulations that have not been regulated in Indonesia.